Analysis of the Role of Digital Technology in Driving Business Model Innovation in MSMEs: Implications for Enhancing Operational Efficiency and Sustainable Economic Growth - Yani, Ahmad; Manafe, Mesri Welhelmina Nisriani; Santosa, Sonny (PT. LITERASI SAINS NUSANTARA, 2025)
This study analyzes the role of digital technology in driving business model innovation in Micro, Small, and Medium Enterprises (MSMEs) and its implications for enhancing operational efficiency and sustainable economic growth. Using a qualitative approach based on a literature review, this study examines literature from Google Scholar for the 2020-2025 period, with a rigorous selection process yielding 20 articles as the basis for analysis. The findings indicate that the adoption of digital technology, including e-commerce, social media, cloud-based systems, and operational automation, enables MSMEs to enhance their competitiveness, expand market reach, and optimize business management. Case studies from various sectors, such as Kopi Kenangan, Sage Footwear, CV Sinar Baja Electric, and Du Anyam, demonstrate that digital technology contributes to accelerating business processes and creating more adaptive and environmentally friendly business models. However, challenges such as limited digital literacy, infrastructure access, and MSME readiness in adopting technology remain significant barriers. Therefore, more inclusive policies, improved access to digital training, and collaboration between the government, private sector, and business communities are necessary to support the optimal digital transformation of MSMEs.